Comparative analysis of physicochemical characteristics and in vitro biological activities of polysaccharides from γ-irradiated and nonirradiated Schizophyllum commune. (August 2022) - Yin, Chaomin; Shi, Defang; Chen, Zheya; Fan, Xiuzhi; Yao, Fen; Lu, Qi; Gao, Hong
Abstract: In this study, the physicochemical characteristics and in vitro biological activities of polysaccharides from γ-irradiated (6, 12 and 18 kGy irradiation doses) and non-irradiated Schizophyllum commune (Fr.) were analyzed. The results showed that the average molecular weight significantly decreased with increasing irradiation dose, whereas the solubility was increased after irradiation. Increased total carbohydrate content, lightness and yellowness as well as slightly decreased thermal stability were observed with increasing irradiation dose. Irradiation treatment decreased the hydroxyl radical scavenging activity and α-amylase inhibitory activity, but increased the reducing power, although no dose-response relationship was observed. When compared to SPGN, SPG6 showed a higher inhibition rate toward HeLa and A549 cells, while SPG18 showed a higher inhibition rate toward HepG2 cells. Overall, SPG18 induced a higher rate of cell apoptosis in HeLa, HepG2 and A549 cells than SPGN did. These results suggested that γ-irradiation treatment of S. commune at an appropriate dose can effectively improve the physicochemical properties and enhance the antiproliferation activity of SPGs. Highlights: Water-soluble polysaccharides were isolated from γ-irradiated S. commune. γ-Irradiation increased purity of SPGs, but reduced its average molecular weight. γ-Irradiation improved the solubility and thermal stability of SPGs. γ-Irradiation brought enhancement of partial bioactivity in SPGs.